Temporalidades na organização e no domicílio: tensões e conciliações no dia a dia de gerentes de lojas no varejo farmacêutico da Grande Belo Horizonte - Magnus Luiz Emmendoerfer (2009)
The thesis analyzes the tensions and conciliations between the organizational and at home demands experienced by managers in the pharmaceutical retail stores in the Great Belo Horizonte area, Minas Gerais, Brazil. The method of case study was applied following methodological strategies of time use researches under a descriptive-explicative perspective. The data was collected with diaries, interviews and questionnaires, was analyzed with statistical methods and confronted with the specialized literature in the field. Thus, the analysis of activities carried out by people in store managerial positions was distributed along of a working day and of a free day. The result showed that time in this situation may be observed as a social construction. The analysis was enriched with comparison between researches time use and the use of time of those who lived in the same house. The result indicate intensification of time devoted to remunerated work with consequently effects on how store managers use time in other spaces of life. The result also showed that store managers experienced these situations as a source of tension which demanded singular practices to conciliate the use of time between store and other daily activities. Finally, the picture of daily life of store managers in the pharmaceutical sector indicates that well-being and quality of life concepts cannot be analyzed disarticulates from the social and organizational context. To know the totality of the dynamic relationship between remunerated and non remunerated activities as well as the tensions and effects caused by occupation a stress is essential for understanding contemporary life.Its essential for the understanding of the contemporary daily life.